The right to interpretation and translation in criminal proceedings - Evert-Jan van der Vlis (JoSTrans: The Journal of Specialised Translation)
More and more people are taking advantage of the freedom of movement of persons and the freedom of establishment within the European Union (EU). Thanks to the current situation, where movements across internal borders are no longer controlled, it has become easier to travel to another Member State (Europa: Schengen). The advent of low-budget airlines such as Easy Jet and Ryanair, among other factors, enables millions of people to go abroad for a holiday every year. Moreover, a growing group of people moves to another EU Member State to live or work there temporarily, or with the intention to settle there permanently. The increasing mobility is not limited to holidays and (labour) migration; drug trafficking, human trafficking and many forms of financial fraud also benefit from the open borders. Criminal organisations can easily move from one country to another. Judicial co-operation in criminal matters and the exchange of information are essential in order to prevent criminals and offenders who move from one Member State to another Member State from escaping punishment. Judicial co-operation in criminal matters can only work well if there is enough attention paid to the issue of safeguarding the legal rights of the suspect/defendant. An important aspect of that legal protection is the right to have the assistance of an interpreter and translator, for suspects/defendants who do not speak the language used in court. This article is all about the manner in which that right is given shape within the EU. It was completed on 17 December 2009.